Holocene landscape reconstruction of the Wadden Sea area between Marsdiep and Weser: Explanation of the coastal evolution and visualisation of the landscape development of the northern Netherlands and Niedersachsen in five palaeogeographical maps from 500 BC to present. Issue 2 (20th May 2015) - Vos, P.C.; Knol, E.
Abstract: This paper describes the background of five palaeogeographical maps between the Marsdiep and the Weser River, and discusses the natural and anthropogenic processes driving the coastal changes during the last part of the Holocene. Before 2500 BC, during the first half of the Holocene, tidal basins were formed in the lower lying Pleistocene valley system as a result of the Holocene sea-level rise. The tidal basins were filled during the second half of the Holocene and on the deposits from the Pleistocene in the hinterland large coastal peat bogs developed. These peat bogs were vulnerable and sensitive to marine ingressions when the peat surface subsided due to drainage, compaction and erosion. During the Subatlantic (450 BC to present), the different ingression systems in the coastal area between Marsdiep and Weser had their own histories in timing and evolution. The ingressions were naturally caused by lateral migration of coastal barrier and tidal-inlet systems or by changes in the natural drainage system in the hinterland. From the Late Iron Age onwards, humans started to be the major cause of ingressions. By reclaiming and cultivating the seaward margins of coastal peat bogs, these areas subsided significantly and were flooded by high storm surges. When coastal areas were embanked during the historical period, the situation for the lower lying peat lands became more dramatic. When the sea dikes breached, the peat land was flooded, leading to casualties and huge material damages and loss of land. Drowning of the peat lands of the Jade and Dollard in the 14th and 15th centuries are examples of such catastrophes.